2019
DOI: 10.1111/joor.12861
|View full text |Cite
|
Sign up to set email alerts
|

Food bolus‐forming ability predicts incidence of aspiration pneumonia in nursing home older adults: A prospective observational study

Abstract: Background Food boluses in the pharynx without enough bolus formation sometimes cause aspiration among older adults; however, the relationship between food bolus‐forming ability and incidence of aspiration pneumonia is unclear. Objective To investigate the relationship between food bolus‐forming ability and incidence of aspiration pneumonia by evaluating the condition of chew‐swallow managing food transported into the pharynx. Methods A prospective observational study conducted in a nursing home for the elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…However, in the present study, witnessed meal dysphagia was reported by family members and caregivers in patients with AsP, whereas meal dysphagia was not reported for any patients with CAP. Meal dysphagia is influenced by a decreased food bolus-forming ability [ 41 ]. Insufficient food-bolus formation and chewing owing to missing teeth, as well as deterioration in tongue movements, increase the risk of aspiration [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, witnessed meal dysphagia was reported by family members and caregivers in patients with AsP, whereas meal dysphagia was not reported for any patients with CAP. Meal dysphagia is influenced by a decreased food bolus-forming ability [ 41 ]. Insufficient food-bolus formation and chewing owing to missing teeth, as well as deterioration in tongue movements, increase the risk of aspiration [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meal dysphagia is influenced by a decreased food bolus-forming ability [ 41 ]. Insufficient food-bolus formation and chewing owing to missing teeth, as well as deterioration in tongue movements, increase the risk of aspiration [ 41 , 42 , 43 ]. In Japan, older adults who live in nursing homes receive 24-h supervision by caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been reported that 71% of elderly patients with pneumonia develop silent aspiration while sleeping [ 6 ], and the main cause of aspiration pneumonia in older patients is thought to be silent aspiration of oral bacteria [ 7 ]. Risk factors for the incidence of aspiration pneumonia include cognitive decline [ 8 ], dysphagia [ 9 ], failure to use dentures [ 10 ], the motor component of the Functional Independence Measure (FIM) score [ 11 ], poor nutritional status [ 12 ], poor oral environment [ 13 ], reduced chewing ability [ 14 ], low albumin level [ 15 ], and tube feeding [ 16 ]. These factors increase the amount of aspiration and oral bacteria and decrease resistance to invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Missing teeth, especially premolars and molars, cause major chewing difficulty 4 . In older people, poor masticatory function can lead to adverse health outcomes 5‐10 . Accordingly, missing teeth should be replaced by dental prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…4 In older people, poor masticatory function can lead to adverse health outcomes. [5][6][7][8][9][10] Accordingly, missing teeth should be replaced by dental prostheses.…”
Section: Introductionmentioning
confidence: 99%